Declining Enrollments in Community Colleges: America’s Economic Divide - Carnevale, Anthony (International Higher Education, 2021)
Enrollment at US community colleges plunged during the COVID-19 pandemic. The enrollment decline is a particularly devastating setback for workers, because of how valuable postsecondary education has become in the US labor market. This highlights the growing divide in the United States between those with postsecondary education and those without it.